Creativity in Titirimundi, international festival of puppet theatre in Segovia: Creativity from the city, the plays to the advertising posters - Martín-Casado, Teresa-Gema (Street Art & Urban Creativity, 2025)
This article shows the importance of the Titirimundi Festival for creativity in its genre. An international puppet theatre festival held in Segovia in the month of May each year. A festival with worldwide prestige and outstanding in the creativity of puppetry, from the theatre plays represented to the communication through its advertising posters, of which an analysis of the last 5 years is proposed. An event that every year demonstrates its creativity not only because each piece represented is above all creative: original by the person who represents it and created for that purpose, but also because of the way it is communicated from the poster, which is also inspiring. A festival that breaks the mould and expresses itself from new, original and outstanding designs in all its actions, showing in each of them great artistic-creative expression.